The Biometric Measurement of Alcohol Consumption - Snell, Lawrence D.; Ramchandani, Vijay A.; Saba, Laura; Herion, David; Heilig, Markus; George, David T.; Pridzun, Lutz; Helander, Anders; Schwandt, Melanie L.; Phillips, Monte J.; Hoffman, Paula L.; Tabakoff, Boris (Alcoholism, clinical and experimental research, 2012)
Background:  Proper ascertainment of the history of alcohol consumption by an individual is an important component of medical diagnosis of disease and influences the implementation of appropriate treatment strategies that include prescription of medication, as well as intervention for the negative physical and social consequences of hazardous/harmful levels of alcohol consumption. Biological (biometric) diagnostic tests that provide information on current and past quantity and frequency of alcohol consumption by an individual, prior to onset of organ damage, continue to be sought. Methods:  Platelet monoamine oxidase B (MAO‐B) protein was quantitated in 2 populations of subjects who had histories of different levels of alcohol consumption. Levels were assayed by immunoblotting or by ELISA. The development and evaluation of the new ELISA‐based measure of platelet MAO‐B protein levels is described. Results:  One subject population constituted a nontreatment‐seeking, cross‐sectional subject sample, and the other population was a longitudinally followed, hospitalized group of subjects. An algorithm combining measures of platelet MAO‐B protein with the plasma levels of carbohydrate‐deficient transferrin (CDT) and with liver enzymes (aspartate aminotransferase or γ‐glutamyltransferase [GGT]) can detect hazardous/harmful alcohol use (HHAU) with the highest sensitivity and specificity in the cross‐sectional nontreatment‐seeking population. In the treatment‐seeking population, low MAO‐B protein levels at admission are associated with heavy drinking prior to admission, and these protein levels increase over a period of abstinence from alcohol. Conclusions:  The platelet MAO‐B protein measurement is particularly effective for male alcohol consumers. The combined use of MAO‐B protein measures together with measures of CDT and GGT does, however, improve the diagnostic utility of both markers for ascertaining HHAU in women. Furthermore, measurement of changes in platelet MAO‐B protein levels during treatment for alcohol dependence may help monitor the success of the treatment program.